Acute effects of a conventional high-intensity strength training session under simulated orthostasis on a new robotic leg press - Kümmel, J.; Rosenberg, A.; Mester, J.; Gruber, M.; Zange, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Lower body negative pressure (LBNP) is a gravity independent method to simulate orthostasis. Due to the muscle pump function in exercising leg muscles, an increase in hydrostatic pressure by gravity or LBNP increases the arteriovenous pressure difference and in consequence muscle perfusion (Egana et al., 2010). This study is the first application of combining a robotic leg press (RBL) that allows free modelled profiles of force and velocity with a LBNP chamber. We tested the hypotheses that LBNP during simulated high-intensity leg press exercise i) increases total hemoglobin content (tHb) and oxygen saturation (SmO2) for m. vastus lateralis, and ii) reduces the increase in systolic blood pressure (sBP) and cardiac output (CO). Methods: Nine healthy male subjects (age: 28+-4yrs) participated in this study. In a cross-over design, all subjects performed 3 sets of knee extensions in a supine position at 0 (CON), -20, and -40mmHg LBNP. The RBL produced a constant force at 80% of the individual 1RM. SmO2 and ƒ¢tHb were continuously measured by near-infrared spectroscopy. SBP and CO were determined from measurements of continuous finger blood pressure, thorax impedance, and electrocardiogram. Results: After the first exercise set, Delta tHb increased in all three conditions indicating a reactive hyperemia. With LBNP, Delta tHb was higher when compared to CON (0mmHg: 3.5+-0.9umol/L, -20mmHg: 8.2+-0.9umol/L, -40mmHg: 12.7+-0.9umol/L, P<0.05) during LBNP baseline. Average Delta tHb did not significantly change during exercise sets in comparison to corresponding intervals of rest. During rest, no differences to baseline values in SmO2 and sBP between LBNP and CON were observed, whereas CO was significantly lower with LBNP (0mmHg: 3.8+-1.3L/min, -20mmHg: 2.2+-1.5L/min, -40mmHg: 2.1+-1.8L/min, P=0.04). During exercise, no differences in SmO2, sBP, and CO were found between CON and LBNP. Discussion: The increase in ÄtHb with LBNP indicates capillary blood pooling in the vastus muscle. However, ÄtHb increase with LBNP did not affect the time course of SmO2 during the entire test protocol. Moreover, only at rest but not during exercise, sBP showed the known modulations of the cardiovascular system to orthostasis. This indicates that the participants of the study were not able to profit from improved muscle perfusion using muscle pump and hydrostatic pressure during LBNP with the specific time course of force used in the present leg press training